Bibliometric analysis of South American research in sports science from 1970 to 2012 - David Cristóbal Andrade; Boris Alejandro López; Rodrigo Ramírez-Campillo; Ana Rosa Beltrán; Roxana Pamela Rodríguez (Motriz: Revista de Educacao Fisica, 2013)
Sports science article publication in South American countries (n=11) was studied between 1970-2012, using all citation database of ISI Web of Knowledge. We evaluated: number of published articles; the number of publications divided by the number of people in science and technology (number pub/number peo); the top incidence of research subjects; public or private institutional predominance; impact factor (IF); average citations per document per country; and frequency of published articles per journals per country. Brazil showed the highest number of published articles, followed by Argentina. Bolivia showed the highest number pub/number peo, followed by Peru. Most studied themes were physiology, orthopedic and rehabilitation. Public institutions showed a higher published articles number than did private institutions. Peru and Bolivia were the only countries with a mean IF of 2 or higher. Average citation was higher in Peru (higher coefficient variation). In conclusions, our results show that, in most South American countries, their published articles rate has increased over time. This could be related to new government and institutional policies. However, production was low compared with other areas of science.